Laryngeal infiltrative lipoma in a nine‐year‐old Rottweiler. Issue 2 (27th May 2019) - Caraty, Johan; Belluzzi, Elena; Hassoun, Roy; Esmans, Maya; Bongartz, Alexandre
Abstract : This report describes an infiltrative laryngeal lipoma in a nine‐year‐old female neutered Rottweiler, that was diagnosed with CT and surgically removed. The dog presented with a 3‐month progressive history of severe stridor, exercise intolerance and dysphagia. CT cranial to the thoracic vertebrae showed a 33 cm 3 hypoattenuating mass between the thyroid and cricoid cartilages. Surgical resection was performed and the dog recovered uneventfully postoperatively and did not show any signs of recurrence over a 2‐year period. Histopathological findings revealed an infiltrative lipoma. This clinical case demonstrated a good outcome after resection of a laryngeal infiltrative lipoma and the benefits of performing advanced imaging.